‘Qu’il est loin mon pays’: staging (be)longing in Massenet’s Sapho - Kavanagh, E (Taylor and Francis, 2023)
At first glance, Jules Massenet's opera Sapho (1897) might appear to water down its source material, substituting the searing social commentary of Alphonse Daudet's novel (1884) with idealised tropes of the Midi. This article, however, seeks to complicate this reading, arguing that Sapho moves beyond the regionalism of its operatic predecessors, while entirely reimagining Daudet's novel for a new medium. It highlights how the themes of nostalgia and belonging are established in Henri Cain and Arthur Bernède's libretto, reiterated by Léon Carvalho's staging, and intensified in Massenet's score, thereby nuancing and enriching our understanding of adaptation for the operatic stage.